The accountant's view from the perspective of entrepreneurship in accounting offices (Research, Society and Development, 2021)
The main objective of this article is to analyze the vision of accountants who undertake their own business, using entrepreneurship as an aid tool in the development of accounting work, in accounting offices in the city of Picos-PI. In this way, accountants can be the individuals responsible for the act of being an entrepreneur, if they have characteristics and skills that facilitate the innovation process, in the face of an environment of globalization and transformation. To carry out this study, a questionnaire was applied to the owners of accounting offices in Picos-PI. Regarding the methodology, this study was structured in three stages: bibliographic survey, structured questionnaire and analysis of quantitative and qualitative data. With regard to the results, it is highlighted that, through the calculation and analysis of the data, the present study revealed that the research participants have an entrepreneurial vision, from the opening processor to managing their own business, demonstrating that they have an entrepreneurial profile.